2018
DOI: 10.1016/j.immuni.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Cells Take Your Breath Away

Abstract: Pulmonary neuroimmune networks have emerged as important regulators of lung homeostasis. In a recent issue of Science, Sui et al. show that strategically positioned pulmonary neuroendocrine cells amplify allergic airway responses via group 2 innate lymphoid cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…33 These cells contain dense granules containing a wide variety of neuropeptides, amines, and neurotransmitters and are innervated by the sympathetic and parasympathetic nervous system. 34 Historically, neuroendocrine cells were thought to play a fundamental role during early lung development. 35 Neuroendocrine cells serve as airway chemoreceptors that monitor airway status and signal this to other lung cells or to the brain through synapses with the nervous system.…”
Section: Novel Rare Airway Epithelial Cellsmentioning
confidence: 99%
“…33 These cells contain dense granules containing a wide variety of neuropeptides, amines, and neurotransmitters and are innervated by the sympathetic and parasympathetic nervous system. 34 Historically, neuroendocrine cells were thought to play a fundamental role during early lung development. 35 Neuroendocrine cells serve as airway chemoreceptors that monitor airway status and signal this to other lung cells or to the brain through synapses with the nervous system.…”
Section: Novel Rare Airway Epithelial Cellsmentioning
confidence: 99%
“…According to the International Terms for Human Cytology and Histology published by the Federative International Committee on Anatomical Terminology (FICAT) under the writing of Wolters Kluwer and Lippincott Williams & Wilkins (2008), these cells are called respiratory neuroendocrine cells (in the trachea) or respiratory endocrine cells (in the bronchial tree). However, these cells are documented under different names in modern international scientific literature, and among a wide range of researchers, are better known as pulmonary neuroendocrine cells located near airway branch points of the trachea and the bronchial tree [1][2][3][7][8][9].…”
Section: ключові словаmentioning
confidence: 99%
“…PNECs control the tone of the bronchi and vascular smooth muscle cells, thus regulating the volume of inhaled air and the lung blood supply. In addition, PNECs directly mediate immune response, simulating its activity, and are also potential stem cells in the airways [9].…”
Section: Reviewmentioning
confidence: 99%
“…Therefore, CGRP, as a neuroimmune connector, can guide a variety of immune cells to produce pro-inflammatory responses [37]. Regulations of macrophages [38], DC cells [39], ILC2 cells [40], and mastocytes [41] contribute to Th2 inflammation and lead to pathological reactions of asthma. In addition, sufficient studies demonstrated that some key immune cells, namely lymphocytes [42], monocytes [43] and macrophages [44] also synthesize CGRP.…”
Section: Discussionmentioning
confidence: 99%